2014
DOI: 10.1021/nn500025t
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogenation-Assisted Graphene Origami and Its Application in Programmable Molecular Mass Uptake, Storage, and Release

Abstract: The malleable nature of atomically thin graphene makes it a potential candidate material for nanoscale origami, a promising bottom-up nanomanufacturing approach to fabricating nanobuilding blocks of desirable shapes. The success of graphene origami hinges upon precise and facile control of graphene morphology, which still remains as a significant challenge. Inspired by recent progresses on functionalization and patterning of graphene, we demonstrate hydrogenation-assisted graphene origami (HAGO), a feasible an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
98
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(99 citation statements)
references
References 59 publications
0
98
0
1
Order By: Relevance
“…232 Over the last few decades, synthetic research has led to development of new graphene-inspired building blocks and several new carbonbased H 2 adsorbents designed to enhance binding enthalpies, such as graphene oxide, graphene origami, and others. [233][234][235] For example, various oxygenated functional moieties, including carboxyl and hydroxyl groups, can be introduced to graphene to form graphene oxide (Fig. 11); subsequent crosslinking of this scaffold with organic ligands can be carried out to prepare three-dimensional H 2 adsorbents.…”
Section: Graphene and Graphene Oxide Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…232 Over the last few decades, synthetic research has led to development of new graphene-inspired building blocks and several new carbonbased H 2 adsorbents designed to enhance binding enthalpies, such as graphene oxide, graphene origami, and others. [233][234][235] For example, various oxygenated functional moieties, including carboxyl and hydroxyl groups, can be introduced to graphene to form graphene oxide (Fig. 11); subsequent crosslinking of this scaffold with organic ligands can be carried out to prepare three-dimensional H 2 adsorbents.…”
Section: Graphene and Graphene Oxide Materialsmentioning
confidence: 99%
“…233 Using MD simulations, the authors showed that a origami nanocage-which can be converted between open or closed configurations via an external electric field-could obtain a gravimetric capacity up to 9.7 wt%. Such a concept, although interesting, has yet to be experimentally verified.…”
mentioning
confidence: 99%
“…For example, with designed hydrogenated edges, a graphene origami can form 3D structures through hydrogenation by a trigger in the electric field for potential hydrogen storage. 47 In another example, a four-legged walking robot that is based on single graphene oxide film with asymmetric surfaces can move forward even on smooth glass substrate step by step, by alternating the infrared light on and off. 48 Structural instabilities (e.g., buckling, ripples, and wrinkles) of 2D nanomaterials lead to change in electronic structures.…”
Section: D Materialsmentioning
confidence: 99%
“…Hydrogenation of graphene has attracted great interests owing to two issues: tuning band gap for graphene used in semiconductor-based electronic devices and possible devotions to hydrogen storage [18,[43][44][45]. There are two kinds of typical free-standing HG structures with distinctive properties: H atoms adsorbed graphene (with only one or two H atoms), and graphane, a fully HG.…”
Section: Band Gap Tuning Of Hgmentioning
confidence: 99%